Clutter distribution analysis of a tropical foliage clutter for different environments based on FSR micro-sensor network: article / Nur Alia Zulkifli and Dr. Nur Emileen Abd Rashid - Zulkifli, Nur Alia (2017)
Comparison of four different environment on measuring the wind clutter using forward scatter radar (FSR) operates in ultra-high and very high frequency (UHF and VHF) bands is analyzed in this paper. Since there are four different types of environment involved comparison between those four environments concentrating on different types of clutter level ranging from low, medium, strong and very strong on each locations were studied. The pattern of wind clutter level measurement characteristics as an objective in this research is investigated and executed using distribution models at different operating frequencies as well as comparing the data distributions of four different locations to identify the best distribution model. Sample of data in form of Real Strength Signal Indicator (RSSI) signals measured is evaluated using five distributions model. This comparison justified that Border suits the best location as the strongest clutter area amidst Seaside and Free space, while Forest is determined as the lowest clutter area as the accurate distribution of clutter model. The five distributions parameters are evaluated using maximum likelihood estimation (MLE) approach followed by Goodness of Fit (GOF) method by using Root Mean Square Error (RMSE) test to prove the best distributions among the five which are Log-Normal, Log-Logistic, Gamma, Weibull and Nakagami. Gamma, Weibull and Nakagami. Gamma distribution model is discovered as the best distribution model in this research for foliage clutter for all cases of frequency bands and four environments.